Electron Transfer in SAM/Cytochrome/Polyelectrolyte Hybrid Systems on Electrodes: A Time-Resolved Surface-Enhanced Resonance Raman Study - Grochol, Jana (2007)
Silver electrodes were covered with mixed self-assembled monolayers (SAMs) of 11-mercaptoundecanoic acid (MUA) and 11-mercaptoundecanol (MU) and subsequently coated with alternating layers of cytochrome c (Cyt) and poly(anilinesulfonic acid) (PASA). The immobilized protein is electroactive and retains its native structure. Compared to the case of systems on gold electrodes, the stability of the assembly was found to be decreased. The redox process of Cyt is accompanied by reversible oxidation-reduction of PASA as revealed by the comparative surface-enhanced resonance Raman (SERR) analysis of assemblies including Cyt and the redox-inactive apo-cytochrome c. Timeresolved SERR experiments show a fast electron exchange between the protein and the polyelectrolyte that may play a supporting role in the electric communication of thicker multilayer assemblies employed as sensors.